HORMONAL AND IMMUNOLOGICAL STUDIES IN DIFFERENT TRIMESTER OF PREGNANCY IN COWS
This investigation was carried out with an objective to study serum progesterone and total immunoglobulin levels of cows in three different trimesters of pregnancy. A total of 10 pregnant cows were selected for the investigation besides 10 normal, healthy and non-pregnant cows at oestrus which were considered as control group. Blood sample collected in each gestational stage and serum sample were estimated through kits supplied by Crest Biosystems. The serum progesterone values (ng/ml) observed in first, second and third trimester of pregnancy were 4.85 ± 1.5, 5.76 ± 0.46 and 4.75 ± 1.36 respectively. The cows at oestrus recorded a value of 0.88 ± 0.14 (ng/ml) for serum progesterone concentration. The analysis of variance revealed a highly significant difference (p<0.01) among various stages of pregnancy and non-pregnant (control) group. The total immunoglobulin concentrations in blood serum (g/dl